Marijuana-associated ST-elevation myocardial infarction: is this a benign drug - Kumar, Sundeep (BMJ Case Rep, 2018)
Marijuana is the most commonly used psychoactive drug in the USA. A 35-year-old man with a medical history of marijuana abuse is admitted to the hospital due to crushing substernal chest pain. ECG shows evolving ST-segment elevation with a rise in cardiac enzymes, consistent with ST-elevation myocardial infarction. A urine toxicology screen is positive for cannabis and negative for cocaine and other stimulant drugs. An emergent cardiac catheterisation reveals no evidence of coronary artery disease or thrombosis. A diagnosis of coronary vasospasm is strongly considered, and the patient is started on calcium channel blocker, with a resolution of symptoms and ECG changes. Marijuana-induced coronary spasm causing myocardial infarction has rarely been reported. Marijuana is becoming a social norm in adolescents and there remains a misconception that it is harmless and even beneficial. Increasing drug abuse remains a public health concern, necessitating population education by physicians for safer healthcare practices.